2011
DOI: 10.1016/j.jad.2011.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Two-year course of depressive and anxiety disorders: Results from the Netherlands Study of Depression and Anxiety (NESDA)

Abstract: Their differential course trajectory justifies separate consideration of pure depression, pure anxiety and comorbid anxiety-depression in clinical practice and psychiatric nosology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
251
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(272 citation statements)
references
References 39 publications
15
251
5
1
Order By: Relevance
“…When these disorders co‐occur, the chronicity and functional impairments rise substantially 16, 17, 18. Yet, even though social dysfunction is among the most pervasive and debilitating symptoms of affective psychopathology and tends to persist long after remission, a thorough examination of social functioning in clinically anxious or depressed patients, as well in those presenting comorbidity and those in remission, is currently lacking 19, 20, 21, 22.…”
Section: Introductionmentioning
confidence: 99%
“…When these disorders co‐occur, the chronicity and functional impairments rise substantially 16, 17, 18. Yet, even though social dysfunction is among the most pervasive and debilitating symptoms of affective psychopathology and tends to persist long after remission, a thorough examination of social functioning in clinically anxious or depressed patients, as well in those presenting comorbidity and those in remission, is currently lacking 19, 20, 21, 22.…”
Section: Introductionmentioning
confidence: 99%
“…NIHR Journals Library www.journalslibrary.nihr.ac.uk As well as chest pain, anxiety comorbid with depression is predictive of a worse depression outcome; 138 our participants reported high anxiety levels and we found some evidence of anxiety as a mediator for depression improvement. In a future trial, more active treatment of anxiety should be tested, particularly when associated with chest pain.…”
Section: An Intervention For Symptomatic Coronary Heart Disease and Dmentioning
confidence: 46%
“…To illustrate the use of the RuleFit algorithm, we apply it to a dataset that was used by Penninx et al (2011) to find predictors of the course of depressive and anxiety disorders. Penninx et al (2011) used logistic regression analysis to find sociodemographic and clinical characteristics that predicted psychiatric status (i.e., presence of a depressive or anxiety disorder) after two years.…”
Section: Illustrationmentioning
confidence: 99%
“…Sample Penninx et al (2011) identified predictors of the course of depressive and anxiety disorders using data from the Netherlands Study of Depression and Anxiety (NESDA; Penninx et al, 2008). This longitudinal study includes 2981 respondents, aged 18 through 65 years.…”
Section: Illustrationmentioning
confidence: 99%
See 1 more Smart Citation